Evaluation of Network Security on basis of Virtualization Techniques in Kali Linux Environment - et.al, Prof. Vinit A. Sinha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: In today’s cyber security space network security has a top priority specially system based on Open Source platform. Kali Linux is the new door for white hat security specialist for hardening security for firm and organization. Kali is secure based distribution from linux family having Debian platform. As it includes over 600 + preinstall security application, so it is needy to keep record of network activity by the system and to the system. As kali linux is power tool for server security, virtualization is secure way to implement that tool. The main purpose of this article to evaluate network security on basis of virtualization techniques for this we track implementation of KVM (Kernel Based Virtual Machine) using three virtualization techniques – virt-manager, kimchi project and SDN (Software Defined Network). Virt-manager is python-based desktop user interface for editing and customization of virtual machine through lib-virt. Kimchi is HTML based virtual machine management tool specially used for KVM. SDN is a technology revaluation which needed priory in cloud and virtualization world for providing network services. In this paper we aim to present advantages of virtualization techniques to explore network security hardening in kali linux.